THE ECONOMIC POLICY DURING THE PRESIDENCY OF AHMED BEN BELLA AND ITS IMPACT ON ALGERIA'S INTERNATIONAL RELATIONS (1962–1965) - Ahmed CHENTI (Ziglôbitha)
Abstract: This study seeks to uncover Algeria's economic history during the presidency of Ahmed Ben Bella, a pivotal period in the nation’s history, when Algeria faced a severe crisis that threatened its social and economic stability. The research examines how Algerian policymakers attempted to address these crises, starting with an exploration of the historical context behind adopting a socialist model inspired by Yugoslavia's self-management approach. It traces the process of nationalization through which the Algerian state reclaimed millions of hectares of fertile land and took control of numerous mines and factories, which, under the Evian Accords, had primarily benefited the former colonial powers. The study also highlights the role of financial aid and assistance in alleviating the hardships of the Algerian people and supporting the initiation of a development process that required significant resources amidst the heavy legacy of French colonialism. Additionally, it analyses the impact of these economic policies on Algeria’s international relations, particularly with France — where the past strongly influenced the present — and with the two global blocs of the era. Keywords: Economic policy, Algeria and France, United States, Soviet Union, Ahmed Ben Bella.